2017
DOI: 10.21101/cejph.a4822
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Screen Time Behaviours in Czech Schoolchildren between 2002 and 2014: HBSC Study.

Abstract: SUMMARYObjective: Screen-based behaviours such as watching television or computer use are among the most prevalent sedentary behaviours adolescents spend time on. There is a lack of recent estimates on prevalence and changes in the amount of time spent on screen-based behaviour across Central and Eastern Europe. The main aim is to assess the trends in the prevalence of current recommendations for the screen time ( Conclusions: As screen time is an important indicator of time spent in a sedentary way, our findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
(65 reference statements)
1
15
1
Order By: Relevance
“…Moreover, detrimental effects of screen-based SB appeared to be patternspecific over time, with the durations of watching TV and playing computer/games observed to be inversely associated with SI gain at two-year and six-year followup, respectively. Although watching TV, the predominantly measured screen-based SB, represents the largest amount of screen-based SB for most children, recent studies suggest that computer use has increased dramatically over the years and has even replaced time spent watching TV, especially in adolescents [63,64]. Marco et al [17] also reported that non-study internet use rather than watching TV was negatively associated with whole body BMC in male adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, detrimental effects of screen-based SB appeared to be patternspecific over time, with the durations of watching TV and playing computer/games observed to be inversely associated with SI gain at two-year and six-year followup, respectively. Although watching TV, the predominantly measured screen-based SB, represents the largest amount of screen-based SB for most children, recent studies suggest that computer use has increased dramatically over the years and has even replaced time spent watching TV, especially in adolescents [63,64]. Marco et al [17] also reported that non-study internet use rather than watching TV was negatively associated with whole body BMC in male adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The Health Behavior in School-Aged Children (HBSC) Study found that only 26% of its sample spent at least 1 h per day in MVPA [30]. Regarding ST, the HBSC study reported that 39% of the children complied with screen time recommendations [31]. In European children, approximately one-third of the children failed to meet current screen time recommendations [32].…”
Section: Discussionmentioning
confidence: 99%
“…The second sub-question, 'About how many hours a day, in your free time, do you usually spend playing games on a computer, games console, tablet (such as an iPad), smartphone, or other electronic device (not including moving or fitness games)? ', represents the gaming part of computer use [54]. Each ST-related question was asked for weekdays and weekend days separately.…”
Section: Energy Balance-related Behavioursmentioning
confidence: 99%